(untitled) (Swiss Medical Weekly, 2018)
BACKGROUND Nonpharmacological home remedies offer the potential for easily accessible and well-accepted management of common disorders in general practice. We aimed to assess general practitioners’ (GPs’) perspectives on these remedies in two French-speaking European countries. METHODS In 2017, we conducted a cross-sectional study among community-based GPs in the Geneva (Switzerland) and Grenoble (France) regions. They completed an anonymous questionnaire about forty common home remedies. We asked how often they prescribed each type of remedy and how effective they found them. Descriptive statistics (proportions with 95% confidence intervals [CIs]) were used to summarise the data. RESULTS 349 GPs returned the questionnaire (172 of 500 Swiss and 177 of 500 French; participation rate 35%; male:female ratio 1:1). In the week before the study, GPs had advised 8.2% patients to use at least one remedy. The remedies that were most frequently prescribed were saline water to treat common colds (69%), mobilising and/or stretching exercises for low back pain (67%) and applying cold water or cold pads for burns (60%). The remedies that were perceived to be most effective were squatting during defaecation as a treatment for constipation (89%), phoning a traditional healer to treat skin diseases or burns (84%) and applying cold water or pads for burns (82%). CONCLUSIONS These findings suggest that GPs find certain nonpharmacological remedies very useful, even though they do not frequently prescribe them in practice. These remedies should receive more attention from researchers, as they could be considered by GPs as useful to treat a large number of benign conditions in primary care.